2019
DOI: 10.1021/acs.jafc.9b00361
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Translocation, and Subcellular Distribution of Azoxystrobin in Wheat Plant (Triticum aestivum L.)

Abstract: The uptake mechanism, translocation, and subcellular distribution of azoxystrobin (5 mg kg–1) in wheat plants was investigated under laboratory conditions. The wheat–water system reached equilibrium after 96 h. Azoxystrobin concentrations in roots were much higher than those in stems and leaves under different exposure times. Azoxystrobin uptake by roots was highly linear at different exposure concentrations, while the bioconcentration factors and translocation factors were independent of the exposed concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 45 publications
7
50
0
Order By: Relevance
“…Similarly, the RCFs of propiconazole were stable after 72 h with average values of 16.5, 10.5, 30.1, 15.0, and 4.4 for pepper, tomato, cucumber, maize, and wheat, respectively. The stable RCFs indicated that the uptake of imidacloprid and propiconazole by different crop roots had reached an equilibrium state …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the RCFs of propiconazole were stable after 72 h with average values of 16.5, 10.5, 30.1, 15.0, and 4.4 for pepper, tomato, cucumber, maize, and wheat, respectively. The stable RCFs indicated that the uptake of imidacloprid and propiconazole by different crop roots had reached an equilibrium state …”
Section: Resultsmentioning
confidence: 99%
“…The root sorption experiment was conducted with different initial concentrations (1,5,10,15, or 20 mg L −1 for both pesticides) to determine the main uptake pathway of imidacloprid and propiconazole by wheat roots. The experiment used the method proposed by Ju et al 32 given in Supporting Information.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the systemic translocation of the fungicide determines whether the fungicide can be quickly absorbed by plants and translocated to various tissues. 10,11 Therefore, absorption and translocation capacities are crucial factors for the antifungal effects of fungicides in vivo. 12−14 At present, there are a few fungicides with bidirectional translocation in plants, such as aluminum triethyl phosphate, penflufen, and fenfuram.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plant pathogens infect crops and grains, which seriously threaten their yield. The application of fungicides effectively controls the occurrence and prevalence of plant pathogens. , According to European Union (EU) statistics, the sales of synthetic fungicides account for more than 40% of the total sales of all pesticides and organic fungicides account for 60% of all fungicides. , However, the pesticide resistance and environmental problems caused by the abuse of pesticides are pushing researchers to develop new agrochemicals with novel structures and modes of action. , Excellent types of fungicides must have high antifungal activity, good systemic properties, and low drug resistance. Among them, the systemic translocation of the fungicide determines whether the fungicide can be quickly absorbed by plants and translocated to various tissues. , Therefore, absorption and translocation capacities are crucial factors for the antifungal effects of fungicides in vivo . At present, there are a few fungicides with bidirectional translocation in plants, such as aluminum triethyl phosphate, penflufen, and fenfuram…”
Section: Introductionmentioning
confidence: 99%